Cinema of Pain : On Quebec's Nostalgic Screen - Loiselle, Andre; Czach, Liz, 1965- (Book collections on Project MUSE., 2020)
Since the defeat of the pro-sovereigntists in the 1995 Quebec referendum, the loss of a cohesive nationalistic vision in the province has led many Quebecois to use their ancestral origins to inject meaning into their everyday lives. A Cinema of Pain argues that this phenomenon is observable in a pervasive sense of nostalgia in Quebec culture and is especially present in the province's vibrant but deeply wistful cinema. In Quebecois cinema, nostalgia not only denotes a sentimental longing for the bucolic pleasures of bygone French-Canadian traditions, but, as this edited collection suggests, it evokes the etymological sense of the term, which underscores the element of pain (algos) associated with the longing for a return home (nostos). Whether it is in grandiloquent historical melodramas such as Seraphin: un homme et son peche (Biname 2002), intimate realist dramas like Tout ce que tu possedes (Émond 2012), charming art films like C.R.A.Z.Y. (Vallee 2005), or even gory horror movies like Sur le Seuil (Tessier 2003), the contemporary Quebecois screen projects an image of shared suffering that unites the nation through a melancholy search for home.